2016
DOI: 10.1002/arch.21331
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND HORMONE INDUCTION OF PUTATIVE CHITIN SYNTHASE GENES AND SPLICE VARIANTS IN Leptinotarsa decemlineata (SAY)

Abstract: Chitin synthase (ChS) plays a critical role in chitin synthesis and excretion. In this study, two ChS genes (LdChSA and LdChSB) were identified in Leptinotarsa decemlineata. LdChSA contains two splicing variants, LdChSAa and LdChSAb. Within the first, second, and third larval instars, the mRNA levels of LdChSAa, LdChSAb, and LdChSB coincide with the peaks of circulating 20-hydroxyecdysone (20E) and juvenile hormone (JH). In vitro culture of midguts and an in vivo bioassay revealed that 20E and an ecdysteroid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Moreover, LdChSA contains two splicing variants, LdChSAa and LdChSAb 26. In the present paper, we found that RNAi of both LdChSA isoforms, or each of LdChSAa , LdChSAb or LdChSB severely affected larval growth, caused larval lethality, and impaired larval-larval molting, larval-pupal ecdysis and adult emergence.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations
“…Moreover, LdChSA contains two splicing variants, LdChSAa and LdChSAb 26. In the present paper, we found that RNAi of both LdChSA isoforms, or each of LdChSAa , LdChSAb or LdChSB severely affected larval growth, caused larval lethality, and impaired larval-larval molting, larval-pupal ecdysis and adult emergence.…”
Section: Introductionsupporting
confidence: 52%
“…Furthermore, chitin is absent in plants and vertebrates. All these results indicate that ChS provides an important target for a potential pest control strategy through RNAi 18, 25, 26.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Fortunately, dietary introduction of bacterially expressed double‐stranded RNAs (dsRNAs) is able to effectively knock down target genes in L. decemlineata (Sun et al ., ; Meng et al ., ; ; Xu et al ., ). Moreover, chitin is absent in vertebrates, and chitin biosynthesis enzymes have been confirmed to be potential targets for novel insecticide development (Shi et al ., ; ). These prompt us to carry out a functional analysis of CDA2 in L. decemlineata larvae and to estimate its potential effect on the larvae.…”
Section: Introductionmentioning
confidence: 99%